The development of MDA-7/IL-24 as a cancer therapeutic - Dent, Paul (2010)
The cytokine melanoma differentiation associated gene 7 (mda-7) was identified by subtractive hybridization as a protein whose expression increased during the induction of terminal differentiation, and that was either not expressed or was present at low levels in tumor cells compared to non-transformed cells. Based on conserved structure, chromosomal location and cytokine-like properties, MDA-7, was classified as a member of the interleukin (IL)-10 gene family and designated as MDA-7/IL-24. Multiple studies have demonstrated that expression of MDA-7/IL-24 in a wide variety of tumor cell types, but not in corresponding equivalent non-transformed cells, causes their growth arrest and rapid cell death. In addition, MDA-7/IL-24 has been noted to radiosensitize tumor cells which in part is due to the generation of reactive oxygen species (ROS) and ceramide that cause endoplasmic reticulum stress and suppress protein translation. Phase I clinical trial data has shown that a recombinant adenovirus expressing MDA-7/IL-24 (Ad.mda-7 (INGN-241)) was safe and had measurable tumoricidal effects in over 40% of patients, strongly arguing that MDA-7/IL-24 could have significant therapeutic value. This review describes what is presently known about the impact of MDA-7/IL-24 on tumor cell biology and its potential therapeutic applications.